Joint contact force and movement deceleration among badminton forward lunges: a musculoskeletal modelling study - Chen, T. L.-W.; Wang, Y.; Wong, D. W.-C.; Lam, W.-K.; Zhang, M. (Sports Biomechanics, 2022)
Joint contact force is the actual force applied on the articular surface that could predict performance and injuries, but rarely reported for badminton sport. The study sought to calculate lower limb joint contact force and decelerative kinematics for badminton forward lunges. Fifteen badminton players performed backhand and forehand forward lunges in random order. The kinematic and kinetic data were input to scale a musculoskeletal model and solve inverse dynamics in the simulations. Outcome variables were compared between lunge conditions using repeated measures MANOVA. Forehand lunge produced higher compressional ankle contact force (p = 0.040, partial 2 = 0.14), faster touchdown hip abduction (p = 0.031, partial 2 = 0.16), and larger horizontal deceleration of the mass centre (p = 0.016, partial 2 = 0.19) and torso (p = 0.031, partial 2 = 0.16) compared to backhand lunge. Despite the statistical significance, we found that the increments of joint loading in forehand lunge were small (<5%) with limited effect size and could be attributed to the larger movement deceleration during braking. These force changes could possess performance merits. However, its linkage to injury risk is unclear and warrants further investigation.